Reflexões sobre libras no ensino fundamental I: comunicação de professores ouvintes com alunos surdos em uma escola pública de Araguaia-TO. - Sousa, Mariza (Universidade Federal do Tocantins, 2022)
Everyone has rights, whether or not they have special needs, access to education, health, work, leisure and other resources that are necessary for them to fully develop and live in society as a human being. However, in order to contribute to the discussion of this theme, the present study will focus on the experiences of teacher-listeners with students / deaf people in the classroom, during all classroom activities, as and when students interact in a way that they can communicate. The established objective is to research and carry out field studies, the importance of every child having access to education, at least an introduction in the Brazilian language of signs, to verify if inclusion is actually being applied correctly, if teachers and students are prepared to receive students and colleagues with this disability and if they believe that this idea can really help the school units, teachers and especially the deaf student. We conducted interviews with a deaf student, an interpreter and a listener teacher, whose results we present at the end of the study.